Neuropsychiatric manifestations of Long COVID in India: a persistent problem 2.5 years after disease onset - Singh, Anurag Kumar; Kumar, Kamlesh; Singh, Mahaveer; Jagawat, Tushar; Nathiya, Deepak; Singh Tomar, Balvir; Jagawat, Savita; Jimenez, Millenia; Lopez, Melissa; Miller, Janet; Koralnik, Igor J. (Frontiers in Neurology, 2025)
BackgroundLong COVID, also called post-acute sequelae of SARS-CoV-2 infection (PASC), is a multi-system syndrome affecting millions of people worldwide. Neuropsychiatric manifestations of Long COVID are particularly debilitating; however, they have not been reported in detail from India.MethodsThis cross-sectional study compared the demographics, comorbidities, symptoms, and neuropsychiatric profiles of patients with Long COVID symptoms that began within 3 months of the initial SARS-CoV-2 infection and persisted for approximately 2.5 years at the time of evaluation. The study was conducted at NIMS University (Jaipur, Rajasthan, India).ResultsOf 1,085 participants, 521 had COVID-19 pneumonia requiring hospitalization, while 564 had a mild initial respiratory presentation and were never hospitalized. On average 2.5 years after acute infection, our principal finding is that Long COVID differs based on initial disease severity. Post-hospitalization patients were older than the non-hospitalized group (43.24 vs. 36.15 years; p < 0.0001), had a higher body-mass index, and a more frequent prior history of lung disease (7.7% vs. 2.7%; p < 0.001). Overall, 69.6% of participants had at least one neurologic symptom, including myalgia (18.5%), dizziness (17.3%), headache (16.6%), pain (15.7%), anosmia (13.3%), brain fog (9.4%), numbness (6.0%), tinnitus (5.5%), and dysgeusia (3.7%), with only dizziness being more frequent in the post-hospitalization than the non-hospitalized group (20.3% vs. 14.5%; p = 0.012). Conversely, non-hospitalized patients had more frequent fatigue (23.2% vs. 6.0%; p < 0.0001), sleep problems (18.4% vs. 7.7%; p < 0.0001), chest pain (8.2% vs. 2.9%; p < 0.0001), and gastrointestinal symptoms (7.8% vs. 2.9%; p < 0.0001), while post-hospitalization patients more frequently complained of shortness of breath (9.6% vs. 2.7%; p < 0.0001). Overall, 4.9% of participants had cognitive dysfunction on the MMSE test, while 10.4% suffered from stress, and 12.7 and 9.2% had anxiety and depression symptoms, respectively, on DASS assessment, without significant differences between the two groups.ConclusionOur study highlights differences in demographics and clinical presentation of Long COVID between post-hospitalization and non-hospitalized individuals in India. The high frequency of neurologic manifestations 2.5 years after disease onset underscores the need for early detection and targeted interventions.